Paint Brush for Hire - Moffatt, Frederick C. (Book collections on Project MUSE., 2018)
"This book chronicles the interesting lives of the nineteenth-century painter James Cameron (1817-1882) and his wife, Emma (1825-1907). James Cameron's remaining known oeuvre contains about twenty paintings, including some from the time he lived here in Knoxville. But he and his wife traveled extensively--including to revolutionary Italy, when Cameron studied the classical and renaissance masters--as Cameron became a working artist, mainly in several places throughout the South. Based on their lives, the author sketches out the life of an itinerant, mainly southern painter in the middle to late decades of the nineteenth century. While Cameron was perhaps of moderate talent, the value of this work should lie in illuminating the day-to-day life of American painters, including the challenges they faced to make a living in the nineteenth century. The author's task is aided considerably by his discovery of a large collection of Cameron papers housed at Mills College in Oakland, California. The most voluminous source material comprised diaries written by Emma. She was a keen observer of their situation and an energetic writer"--